Patterns of Stuttering Comparing two Languages: A Case Report (2015)
In bilinguals, specific patterns of stuttering in each one of the languages may be different. This study reports on the case of a bilingual adult who speaks Spanish and English simultaneously and whose dominant language is Spanish. Speech and language testing was performed in both languages. The samples chosen for the analysis of speech corpus were: spontaneous speech, description of the picture and reading. Some differences in the stuttering distribution were found. Of the disfluent instants, 61.39 % of the total was presented in English and the other remaining 38.61 % in Spanish. In both languages, stuttering by word type was more frequent in function words (i.e. prepositions, pronouns, conjunctions, particles and infinitive forms) than in content words (i.e. verbs, nouns, adjectives). As observed, dysfluency types were similar in Spanish and English, with the greatest percentage being word repetition, followed by phonemic prolongations. These were more frequent in English than in Spanish. Although it is possible to find similarities in the stuttering pattern suggesting general stuttering laws, differences associated not only with language-specific idiosyncrasies but also with the individual’s bilingualism characteristics were also found.